Development of an Electrode Using Carbon Nanotubes as a Support Material for Direct Methanol Fuel Cell - Abdul-Malek Salim, Ramzia (2006)
Global interest in renewable power sources to cut back the current fuel emission levels and to solve the foreseen fuel crisis makes the development of a new fuel cell system a necessity. A fuel cell is an electrochemical device that produces electricity by separating the fuel (generally) hydrogen gas in the presence of a catalyst. Hydrogen Fuel cell is the simplest form of fuel cell but there are major problems with storing and transporting hydrogen due to high combustibility. Another alternative to Hydrogen FC is the Direct Methanol Fuel Cell (DMFC). The net energy density of methanol is higher than any other type of fuel (5.26kwhkg-I). Hydrogen as a fuel has a net energy density of 0.2kwhkg-'. Yet, there are two major problems associated with DMFC, firstly, the fuel anode reactions are much slower than the hydrogen fuel cell reaction, and secondly, methanol crossover through the membrane. To address the former, a catalyst must be used to accelerate the reaction. It is now more or less a standard to use a mixture of Platinum and Ruthenium as the bimetallic catalyst. However the mount of loading, typically 4mg/m2 is too high and tampers the commercialization of the DMFC. This is solved by the use of a properly supported catalyst. Due to electrical conductivity and high surface area of Carbon, it is widely used as the support material. However, the amount of metal catalyst to support material, the loading per em2, and the form of carbon support to be used is not yet standardized. Lately, Carbon Nanotubes (CNTs) have attracted much attention due to their excellent electrical properties, surface inertness and large swface area. CNTs have been synthesized using the Chemical Vapor Deposition (CVD) method. The synthesized CNTs were functionalid using 12M nitric acid, to activate their surfaces to enable anchoring the metal ions to them. Different ratios of catalysWNT were prepared by chemical reduction method of CNTs and metal precursors in a mixture with a reducing agent, ethylene glycol. Ttre metal catalysts to CNT ratios were 40,30 and 20 wt. % PtRdCNT. The anodes were fabricated having different loadings ranging from 0.2 to 1.0 mg/crn2. The anodes were then characterized electrically via I-V curves and eiectrochemicdly using the cyclic voltammetry. The anode design parameters were set to minimize the bimetallic catalyst loading to minimum without tampering the performance. The anode with the least metal to CNT ratio (20 wt.% PtRdCNT) exhibited some very interesting results. The electrochemical activity of that particular anode with loadings of 0.2 mg/cm2 and 0.4 mg/cm2 was the highest among the other two (30 wt.% and 40 wt% PtRdCNT). It was also found that, as the loading anode increases, the electro catalytic activity decreases. This is because the Pt catalyst is not Wig accessible to both the electrical and the ionic conductors.Hence,the catalyst layer has to be as thin as to be in contact with both sides of the cell,yet loading has to be enough to be able to oxidize the methanol. In this project, anodes were fabricated and characterized to give the highest electro catalytic activity with the least precious metal loading